ปัญหากฎหมายเกี่ยวกับการนำหุ้นในตลาดหลักทรัพย์มาเป็นหลักประกันกับธนาคารพาณิชย์ - ฟ้าส่อง พูลผล (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The purpose of this research is to study provisions of law in relation to secured shares in stock exchange, particularly secured party is the commercial banks, which have problem about enforcement of law. In other words, the provisions of law seem to be unclear in practice. This research studies under the Thai Law and compares with American Law and Singapore Law. The study reveals the following findings, there are two forms of taking shares listed in stock exchange as security. Firstly, scripless system shall be created under the Securities and Exchange Act B.E. 2535, section 228/1 and scrip system shall be created under section 753 of the Civil and Commercial Code. Taking shares of scripless as security does not have to deliver certificate of shares hence it cannot be called pledging. Nonetheless, security agreement is legally valid by recording information of security interest of shares in the electronic system. However, last paragraph of section 228/1 dose not state clearly that the banks as secured party can be the secured creditor under bankruptcy laws like the pledgee or not. Moreover, in terms of execution with shares, the Civil Procedure Code covers only the seizure of tangible property, not including intangible property. On the other hand, California Code of Civil Procedure, United States of America and Rule of Court of Singapore applies to the seizure of intangible property. Consequently, The writer is of the opinion that the Securities and Exchange Act B.E. 2535, section 228/1 has to be amended about the status of priority of banks as the secured party. It should be similar to secured creditor according to the bankruptcy law. For execution with shares, this problem can be handled by containing the specific provision for the shares listed in stock exchange in the Civil Procedure Code. These suggestions are beneficial for the banks in order to enforce shares listed in stock exchange correctly with authority by law.